2020
DOI: 10.1177/0003489420937044
|View full text |Cite
|
Sign up to set email alerts
|

Reducing ER Visits and Readmissions after Head and Neck Surgery Through a Phone-based Quality Improvement Program

Abstract: Objective: Evaluate the impact of a patient phone calls and virtual wound checks within 72 hours of discharge on reducing emergency room (ER) visits and readmissions. Methods: Single arm trial with comparison to historical control data of patients undergoing multi subsite head and neck cancer operations or laryngectomy between July 2017 and June 2018 at a tertiary academic medical center. Patients were contacted within 72 hours of hospital discharge. As a supplement to the call, patients were given the opportu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 45 publications
0
21
0
3
Order By: Relevance
“…Prior research on postoperative ER visits has discovered that early postoperative phone calls and telehealth visits from clinical personnel can help minimize ER visits [ 13 , 14 ], implying that early patient engagement and communication can help alleviate the health care system’s burden. Although telehealth visits and phone calls may alleviate some of the strain on health care resources, they are time-consuming and difficult to scale.…”
Section: Introductionmentioning
confidence: 99%
“…Prior research on postoperative ER visits has discovered that early postoperative phone calls and telehealth visits from clinical personnel can help minimize ER visits [ 13 , 14 ], implying that early patient engagement and communication can help alleviate the health care system’s burden. Although telehealth visits and phone calls may alleviate some of the strain on health care resources, they are time-consuming and difficult to scale.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in patients being treated for colorectal cancer, a pilot randomized control trial examining the effectiveness of a nurse-delivered telephone supportive intervention demonstrated a non-significant reduction in presentations to emergency department (21% vs 33%; p = 0.23) and readmission to the hospital (37% vs 47%; p = 0.37), 6 months after surgery [ 16 ]. Conversely, Shah et al demonstrated a significant decrease in ED visits (19.2% vs 6.6%; p = 0.01) but not readmissions (10.2% vs 7%; p = 0.4) in patients called within 72 h of being discharged after multi-site head and neck cancer operations and total laryngectomies [ 17 ], and Iqbal et al demonstrated that discharge phone calls, post-ileostomy creation, significantly decreased readmission for dehydration from 65 to 16% ( p = 0.002), albeit calls were being made daily for 3 weeks [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…This review identified a number of telemedical interventions which do not require the use of specialised equipment and can be implemented with simple Internet-capable devices that patients already have at home. Five studies used the basic camera and microphone functions of smartphones to diagnose otorhinolaryngologic disorders 8 , 14 , 17 , 18 , 40 and three studies used highly sensitive questionnaires, administered over a basic telephone call, to monitor for post-procedural complications and disease recurrence. 7 , 9 , 10…”
Section: Discussionmentioning
confidence: 99%